2014
DOI: 10.1155/2014/486798
|View full text |Cite
|
Sign up to set email alerts
|

The Role of M1 and M2 Macrophages in Prostate Cancer in relation to Extracapsular Tumor Extension and Biochemical Recurrence after Radical Prostatectomy

Abstract: Introduction. The aim of our work was to investigate the causal connection between M1 and M2 macrophage phenotypes occurrence and prostate cancer, their correlation with tumor extension (ECE), and biochemical recurrence (BR). Patient and Methods. Clinical and pathological data were prospectively gathered from 93 patients treated with radical prostatectomy. Correlations of commonly used variables were evaluated with uni- and multivariate analysis. The relationship between M1 and M2 occurrence and BR was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 12 publications
7
119
1
4
Order By: Relevance
“…However, the role of AAMs in metastasis of PCa was previously undefined. Lanciotti et al (19) collected clinical and pathological data from 93 patients treated with radical prostatectomy and analyzed the association between CAMs and AAMs occurrence. They concluded that a higher density of macrophages was associated with poor prognosis and that AAM was significantly associated with tumor extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of AAMs in metastasis of PCa was previously undefined. Lanciotti et al (19) collected clinical and pathological data from 93 patients treated with radical prostatectomy and analyzed the association between CAMs and AAMs occurrence. They concluded that a higher density of macrophages was associated with poor prognosis and that AAM was significantly associated with tumor extension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two recent studies have indicated that TAMs and AAMs participated in the progression of prostate cancer (19)(20)(21). However, the association between differentiation of macrophages and metastasis of prostate adenocarcinoma (PCa) is not well-established.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke contains more than 100 different mutagens and carcinogens and is the cause of approximately 90% of lung cancer cases [16,17]. Recently, it has been reported that TAMs can promote tumor progression, and an abundance of M2 macrophages have been found to infiltrate solid lung tumors, a characteristic that is associated with poor prognosis [18][19][20]. Macrophages can be divided into two main phenotypes: classically activated macrophages (M1) and alternatively activated macrophages (M2).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, macrophages are a primary source of secreted proinflammatory cytokines, and are generally distinguished in two different phenotypes: M1, with tumor inhibitor properties [production of inflammatory cytokines, reactive oxygen species (ROS), and activated immune response] and M2, with tumor-stimulatory properties (promote tissue repair and angiogenesis) [47][48][49][50]. Recently, Lanciotti et al [50] observed that a high density of macrophages in prostate cancer was associated with poorer prognosis. Moreover they found higher prevalence of M2 macrophage phenotype, which resulted and more represented in prostate cancer Gleason score 7 to 8-10 and pT3a stage.…”
Section: The Innate Immunitymentioning
confidence: 99%